Pengaruh Kepemilikan Buku Teks Dan Motivasi Belajar Terhadap Penggunaan Smartphone Sebagai Sumber Belajar Pada Mahasiswa Fakultas Ekonomi UNP - Armiati Armiati; Nopiana Helda (Universitas Negeri Padang, 2019)
This research aimed to measure: (1) Effect of ownership of Textbooks to use the smartphone as a source of learning in students of Faculty of Economics, Universitas Negeri Padang. (2) Effect of motivation to learn to use the smartphone as a source of learning in students of Faculty of Economics, Universitas Negeri Padang. (3) Effect of ownership of textbooks on learning motivation in students of Faculty of Economics, Universitas Negeri Padang. The study was descriptive correlational. The study population was students of Faculty of Economics, Universitas Negeri Padang. The sampling technique used was purposive sampling and the sample size in this study were 97 respondents. The data used are primary data. Data collection techniques used were questionnaires. Data analysis technique used is descriptive analysis and inductive analysis using path analysis techniques. The results showed that (1) the ownership textbooks significantly influence the motivation to learn (2) Ownership textbooks do not significantly affect the use of smartphones as a learning resource but indirect effect through learning motivation, (3) learning motivation influence directly and significantly to the use of a smartphone as a learning resource.